Analysis of Comprehension Difficulties in Chemistry and Their Impact on Student Interest in Learning - Febriani, Febriani; Hayyun, Hayyun; Nilawati, Ratna; Abdullah, Abdullah (Jambura Journal of Educational Chemistry, 2024)
Chemistry is often considered a difficult subject for learners due to its abstract concepts and complex terminology. This can lead to difficulties in understanding the material and a decrease in students' interest in studying chemistry. The aim of this research is to describe and explain the factors of difficulty understanding in solving chemistry material experienced by students. The research method used is descriptive qualitative. The results show that 62.3% of students experience slight difficulty and 37.7% experience moderate difficulty in understanding chemistry material. The interest in learning chemistry of class XII MIA students is categorized as sufficient with a percentage of 46.68%. Factors causing difficulties in understanding chemistry material include a lack of understanding of mathematical concepts, the predominance of lecture methods, limited learning media, and the suboptimal use of chemistry laboratories. The conclusion of this research provides an overview that the factors causing difficulties in understanding chemistry material affect students' interest in learning. Therefore, these findings can be used as evaluation material to improve the quality of chemistry education in schools.